2015
DOI: 10.5559/di.24.3.05
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Loneliness in the Relationship Between Social Anxiety and Subjective Well-Being: Using the Social Phobia Inventory (SPIN) as a Measure

Abstract: The purpose of this study was to test the mediating role of loneliness in the relationship between social anxiety and subjective well-being while taking into account the multidimensionality of social anxiety. Reaching this aim was preceded by examining the psychometric properties of the Croatian translation of the SPIN on a sample of 202 students. The results show support for the one-dimensional structure of the SPIN. However, it has also been shown that several items of the inventory may be redundant and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
2
6
1
Order By: Relevance
“…The results showed that fear of negative evaluation had a negative effect on psychological well-being of female adolescents with psychological problems. The results of this study are in line with the results of Gandaharizadeh et al (1977), which showed that psychological well-being treatment was effective in reducing fear of negative evaluation of obsessive compulsive disorder patients, and is in line with Reis and McNally's (1985), Maričić & Štambuk (2015) Eng et al (2005), who also pointed out the negative relationship between social anxiety and psychological well-being. Explaining the findings of the present study, it can be said that psychological well-being is not only influenced by stressful events but also by individual characteristics that determine how adolescents evaluate events and how they deal with these stressors (Cejudo et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that fear of negative evaluation had a negative effect on psychological well-being of female adolescents with psychological problems. The results of this study are in line with the results of Gandaharizadeh et al (1977), which showed that psychological well-being treatment was effective in reducing fear of negative evaluation of obsessive compulsive disorder patients, and is in line with Reis and McNally's (1985), Maričić & Štambuk (2015) Eng et al (2005), who also pointed out the negative relationship between social anxiety and psychological well-being. Explaining the findings of the present study, it can be said that psychological well-being is not only influenced by stressful events but also by individual characteristics that determine how adolescents evaluate events and how they deal with these stressors (Cejudo et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…High levels of fear of negative evaluation are commonly found in people with social anxiety who are highly susceptible to symptoms of potential social threat (Darman et al, 2018). Since fear of negative evaluation is a cognitive component of social anxiety, research by Reiss & Mcnally (1985) (quoted by Karim & Arooj Naz, 2017), Maričić & Štambuk (2015), Eng, Coles, Heimberg & Safren (2005) A negative relationship was also found between social anxiety and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from earlier investigations supported this finding, reporting the mediating effect of loneliness on the association between social anxiety and subjective well-beings (e.g., Maričić & Štambuk, 2015). For example, examining 202 Spain students, Maričić and Štambuk (2015) identified that the symptoms of social anxiety contributed to its relationship with life satisfaction through loneliness.…”
Section: Discussionmentioning
confidence: 78%
“…Evidence from earlier investigations supported this finding, reporting the mediating effect of loneliness on the association between social anxiety and subjective well-beings (e.g., Maričić & Štambuk, 2015). For example, examining 202 Spain students, Maričić and Štambuk (2015) identified that the symptoms of social anxiety contributed to its relationship with life satisfaction through loneliness. The finding of the current study provided a comprehensive insight into the relationships between social anxiety, loneliness, and life satisfaction, and provided the evidence that the mediating effect of loneliness is also strong with special population group (e.g., left-behind children), different cultures (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, a muted positivity bias may be at the root of loneliness and social isolation that accompanies elevated social anxiety symptoms. Not only does loneliness mediate the relationship between greater social anxiety symptoms and diminished subjective wellbeing (Maričić & Štambuk, 2015), it can also predispose to many chronic health problems via alterations in neuroendocrine, autonomic, and immune function (Cacioppo & Cacioppo, 2014). Therefore, augmenting motivation to engage in neutral/ambiguous social situations may promote physical health through increased social engagement and integration.…”
Section: Limitations Implications and Future Directionsmentioning
confidence: 99%